Greenhouse Gas Emissions Associated With the Mexican Diet: Identifying Social Groups With the Largest Carbon Footprint - López-Olmedo, Nancy; Stern, Dalia; Bakhtsiyarava, Maryia; Pérez-Ferrer, Carolina; Langellier, Brent (Frontiers in Nutrition, 2022)
Background: Most studies of the climate footprint of diets have been conducted in countries in the global north, but the majority of the world population lives in global south countries. We estimated total dietary greenhouse gas emissions (GHGE) in Mexico, examined the contribution of major food and beverage groups, and assessed variation across social groups. Methods: We linked individual-level dietary data from the Mexican National Health and Nutrition Survey 2018 to the SHARP Indicators Database, containing GHGE estimates for 182 primary food and beverages. Results: Mean dietary GHGE was 3.9 kilograms of carbon dioxide equivalent per person per day. Dietary GHGE is highest among those in young adulthood and middle age versus adolescents and older adults, and among males, those with higher educational attainment, higher socioeconomic status, that do not speak an indigenous language, and that live in urban areas. Conclusions: The Mexican diet has a much lower carbon footprint than diets in other Latin American countries for which such estimates are available. In contrast to patterns observed in Argentina and Brazil, dietary GHGE was lowest in those in lower socioeconomic and educational strata and in rural areas. A better understanding of the differences in diet sustainability between and within countries will be needed for developing global and local strategies that meet the environmental sustainability goals.